Development of a Padlet-Based Interactive Digital Comic to Enhance Learning Outcomes and Appeal of Science for Elementary School Students - Krisna Murti Anugraha; Rufi'i; Nurmida Catherine Sitompul (The Indonesian Institute of Science and Technology Research, 2026)
In elementary science education, traditional didactic approaches frequently lead to low learning outcomes and disengaged students. By creating and examining the effectiveness of an interactive digital comic based on Padlet to improve student learning outcomes and subject appeal, this study filled this knowledge gap. With a perfect Scale Content Validity Index (S-CVI/Ave) of 1.00, the product achieved a Highly Valid classification across content, media, and instructional design after undergoing rigorous expert validation using the Dick and Carey model. Its high acceptance (OMS = 0.46) was further validated by a small group feasibility evaluation. Twenty-four fourth-graders participated in a one-group pretest-posttest design to evaluate the comic's efficacy. The mean learning score increased dramatically from 56.16 on the pretest to 97.92 on the posttest, according to the results. This improvement was statistically significant (t = 10.24; p < .001), indicating that the comic promoted almost flawless subject mastery. In summary, it has been established that the interactive digital comic is a very legitimate, practical, and successful teaching tool for improving science education and boosting student interest in elementary school.